Armoede en ongelijkheid bij ouderen: Een vergelijkende studie van de pensioenstelsels in België en Nederland - Ingrid Keupers (Luxembourg Income Study (LIS), 2009)
– Pension systems in European countries are under review due to demographic changes. As a solution to the graying population, second and third pillar pensions are advocated. However, it is important not to lose sight of the social consequences of encouraging these private pensions. In this master thesis the paradox of redistribution from Korpi & Palme (1998) is tested on two cases namely Belgium and the Netherlands. Based on micro data on household income as found in the LIS database, pensioners are compared on their poverty rates and inequality. The redistribution paradox states that poverty will be the highest in pension systems that are targeted and will be the lowest in universal systems. In Belgium (targeted minimum pension) poverty rates are much higher than in the Netherlands (universal minimum pension). Poverty rates are higher for elderly women than for elderly men and this gender difference is greater in the Netherlands than in Belgium. The paradox of redistribution further states that inequality will be higher when the first pillar provides flat-rate pensions and will be the lowest for wage coupled pensions that out compete more unequal private pension provisions. In the Netherlands (flat-rate pension), inequality is higher than in Belgium (wage coupled pension) when calculated on the basis of pension income. When disposable income is taken as reference than the inequality is slightly larger in Belgium than in the Netherlands. There is however a much larger reduction in inequality compared to pre-pensioned individuals in Belgium than in the Netherlands. The inequality in income is higher for men than for women both in Belgium and in the Netherlands. In order to minimize poverty and inequality, it is thus advised to further strengthen the pensions systems in both Belgium and the Netherlands not to reduce them.
Keywords: 330; paradox of redistribution; poverty; inequality; Belgium; the Netherlands; pension system; Gesetzliche Rentenversicherung; Altersvorsorge; Armut; Soziale Ungleichheit; Einkommensumverteilung; Geschlecht; Belgien; Niederlande